Kuat Tekan Beton Mutu fc 30 MPa Dengan Penambahan AdmixtureSebesar 0.05%, 0.09%, 0.13% Dari Berat Semen - Melisa, Maya (Jurnal Vokasi Teknik Sipil, 2023)
This paper aims to determine the compressive strength of cylindrical concrete with mixed quality design fc’ 30MPa with additional Air Entraining Admixture to determine the effect of the added material on the compressive strength of concrete. Based on brochure Air Entraining, this additive is in nature polymer which dissolves in water which functions to increase the weight of the concrete and reduce the use of cement in the mixture. The concrete mix trials were divided into three treatments/three compositions, namely with Air Entraining 0.05%, 0.09% and 0.13% respectively by weight of cement. The composition of the concrete mixture in mix design composed of 22.26kg of cement, 48.7 kg of fine aggregate, 22.08 kg of coarse aggregate of 5-12 mm size, 41.04 kg of coarse aggregate of 10-20 mm size, 8.50 kg of water. The compressive strength test results at cylindrical concrete with additives Air Entraining 0.13% at 28days of age of 26.85 MPa. Compressive strength of cylindrical concrete with additives Air Entraining 0.09% at 28 days of age of 28.25 MPa. Furthermore, for the compressive strength of cylindrical concrete with added materials Air Entraining 0.05% at 28 days of age of 30.3 MPa.